HOW EFL LEARNERS NOTICE AND CORRECT GRAMMAR ERRORS THROUGH PEER FEEDBACK: A QUALITATIVE EXPLORATION - Az Zahra, Olivia; Wijayatiningsih, Testiana Deni; Setiawan, Anjar (JR-ELT (Journal of Research in English Language Teaching), 2025)
Writing accuracy is one of the most persistent challenges faced by EFL learners, who often struggle with grammatical precision, lexical appropriateness, and the ability to construct coherent and meaningful sentences. These difficulties reduce the clarity and communicative value of students’ writing, highlighting the need for instructional strategies that enhance linguistic accuracy. This literature-based study aims to examine how EFL learners notice and correct grammar errors through feedback by reviewing empirical findings from 14 articles which were published between 2019 and 2025. The article discusses the theoretical foundations of peer feedback, including sociocultural theory, noticing theory, and process writing, and analyzes its effectiveness in four major areas: grammatical accuracy, vocabulary development, learner autonomy, and digital learning environments. The reviewed studies consistently show that peer feedback helps learners identify errors more effectively, promotes deeper revision, and encourages metacognitive engagement, particularly when supported by structured rubrics and teacher guidance. Additionally, digital platforms enhance the quality and clarity of peer comments through features that facilitate real-time editing and transparent documentation. Overall, the findings confirm that peer feedback is an effective and adaptable pedagogical tool for improving writing accuracy in EFL contexts. This study contributes by providing a structured synthesis of recent research and offering implications for instructional practice as well as directions for future investigation.